Atravessamentos dos discursos sobre sexualidade e gênero nos enunciados dos alunos estagiários de psicologia. - Arruda, Laura Valença (2020)
This study aims to understand the discourse on the movements of discourses on sexuality and gender in psychology students who are carrying out a professional practice in the curricular internship, without an academic period between 2018 and 2019, in the psychology course at institutions in the city of Rio de Janeiro. Greater Recife. These statements had the following guiding objectives: will there be a demand related to issues of sexuality and gender in the school clinic of the students / trainee students / interns and what are those demands that demand? What are the possible resonances on the interns who are not accepted in these demands? Would there be? How do the interns evaluate the internship in clinical psychology regarding sexuality / gender issues? Statements from the students about their experiences in the curricular internship and the meanings that they attributed to the issues of sexuality and gender were analyzed. Seven students who were in the compulsory curricular internship of three different educational institutions participated in this research. During the interviews with the participants, it was possible to notice that, during their formation, the discussion about sexual diversity and gender identity were not a priority subject in the curriculum, depending even on the willingness of the teachers to pass the course. content related to sexuality and gender; and also in the interest of the students themselves. It was noted that the discussions were not about broad sense of sexual diversity, affectivity, gender identity, which seek to understand the human being globally and their various ways of acting, thinking and behaving in relation to their sexuality. It was also analyzed the view that these same students have in relation to their educational institutions, if they contribute to an inclusive discourse of sexuality and gender identity and to the subversion of normative speech. This is a qualitative research, using the method of analysis using Foucault's theory as the basis for tracing the path.